2000
DOI: 10.1002/1521-3757(20001215)112:24<4747::aid-ange4747>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Rekonstitution von Kanalproteinen in (polymerisierten) ABA-Triblockcopolymer-Membranen

Abstract: Mechanisch stabile Blockcopolymer‐Protein‐Hybridmaterialien werden hier beschrieben. Dazu wurden großflächige, frei stehende, 10 nm dicke Membranen aus polymerisierbaren amphiphilen Triblockcopolymeren hergestellt, in denen trotz dieser recht großen Dicke Kanalproteine rekonstituiert werden konnten. Die Proteine blieben selbst nach Polymerisation der Membran voll funktionsfähig, wie Leitfähigkeitsmessungen ergaben. Denkbare Anwendungsgebiete für diese Polymer‐Protein‐Hybridmaterialien sind Diagnostik, Sensorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
0
4
0
2
Order By: Relevance
“…[113] Außerdem berichteten Naumann et al über den Einfluss der Polymerlinker auf die Phospholipiddiffusion in der Membran: [114] Die Phospholipiddiffusion wurde behindert, was wahrscheinlich auf eine Lipopolymer-induzierte Protrusion der Membran und/oder Clusterbildung des Lipopolymers zurückzuführen ist, die zu einer Membrankrümmung führen. [115][116][117] und Montemagno [118][119][120] über Polymersome aus Poly(2-oxazolin)-block-poly(dimethylsiloxan)-block-poly(2-oxazolin)-Triblockcopolymeren als biomimetische Membranen erwähnt werden.…”
Section: Selbstorganisation Von Endfunktionalisiertenunclassified
“…[113] Außerdem berichteten Naumann et al über den Einfluss der Polymerlinker auf die Phospholipiddiffusion in der Membran: [114] Die Phospholipiddiffusion wurde behindert, was wahrscheinlich auf eine Lipopolymer-induzierte Protrusion der Membran und/oder Clusterbildung des Lipopolymers zurückzuführen ist, die zu einer Membrankrümmung führen. [115][116][117] und Montemagno [118][119][120] über Polymersome aus Poly(2-oxazolin)-block-poly(dimethylsiloxan)-block-poly(2-oxazolin)-Triblockcopolymeren als biomimetische Membranen erwähnt werden.…”
Section: Selbstorganisation Von Endfunktionalisiertenunclassified
“…We chose PBD 22 ‐PEO 14 (PBD‐PEO 1800) diblock co‐polymer (MW PBD:PEO of 1200:600) as a membrane matrix since it forms 10–12 nm thick polymer bilayers that provide an ideal match for CNTP length. Block‐copolymer membranes were previously used to incorporate a variety of membrane proteins, such as aquaporin Z, ATP synthase, GPCRs, and OmpF porins; therefore, we expected that CNTPs would also incorporate into this membrane ( Figure a). To insert CNTPs into the block‐copolymer membranes, we modified previously developed procedures for inserting CNTPs into lipid matrices, by adding elevated temperatures and constant stirring necessary for PBD‐PEO 1800 to form vesicles.…”
mentioning
confidence: 99%
“…Recently, it was reported that synthetic membranes serve as mimics for biological membranes, and were successfully used to incorporate membrane proteins. [14][15][16][17][18] In particular, vesicles resulting from the auto-assembling of poly(2-methyloxazoline)-block-polydimethylsiloxane-block-poly(2-methyloxazoline) copolymer (PMOXA n -PDMS m -PMOXA n ), have been shown to enable functional reconstitution of channel-forming proteins, such as OmpF, LamB, or Aquaporin Z. [19][20][21][22] In addition, amphiphilic copolymer vesicles have been used to design and build nanoreactors, which protect enzymes encapsulated in their inner cavity and enable them to act in situ, [23] or enable the tandem action of soluble and membrane-bound proteins.…”
mentioning
confidence: 99%